Further studies on characterization of previously isolated free-living amoeba - de Guzman, Teresita S.
Free-living amoeba obtained by collection of water samples from canals along Quezon City area and which were found pathogenic to mice were handed over from a previous study conducted for further characterization and isolation and pure culture. These were designated as RPA-1 strain for the purpose of this study. Pure cultures of amoeba were obtained by cloning a single cyst and/or trophozoite from the original isolates RPA-1. At the same time, RPA-1 isolates were maintained by subcultures and water samples from the original canal source was taken and cultured for the presence of amoeba for comparison. RPA-1 viable cysts and trophozoites, pure culture isolate of this strain and isolates from the original canal source were injected to Swiss white mice via the intranasal and oral routes. All the animals inoculated by the 2 routes failed to develop either symptoms or lesions simulating those of primary meningo-encephalitis. The result of intranasal inoculation was contrary to the result obtained in the previous study. No pathologic changes nor lesions resulted from oral inoculation which was in accordance to the findings of other authors (Carter, 1970; Culbertson, 1968, 1969). The isolates therefore were considered either non-pathogenic or had loss their virulence due to prolonged subculturing. To rule out the letter possibility, intracerebral passage of the isolates to mice, for as many as 3 continuous passages, was done; but still the isolates failed to cause primary meningo-encephalitis to the test animals. However, amoeba were recovered from brain suspensions of intracerebrally infected mice.
Thesis (MPH)--University of the Philippines Manila.
Keywords: Amoeba